Principles of Physical and Organic Chemistry - Jarvis, Alan. (Walton-on-Thames : Nelson, 1997)
Nelson's Advanced Modular Science series is based on the London Examinations A and AS level modular science syllabuses. Each book offers complete and self-contained coverage of the topics required for study in the relevant module.
Includes index.
Keywords: Chemistry, Physical and theoretical; Chemistry, Organic; Chemistry, Physical and theoretical -- Problems, exercises, etc; Chemistry, Organic -- Problems, exercises, etc; Popular Science and Nature